EDUCATION LEVEL IN THE RELATION TO ADOLESCENTS PREGNANCY IN INDRAMAYU 2019 - Rudiansyah Rudiansyah; Dartiwen Dartiwen (Insights in Public Health Journal, 2020)
Adolescents’ pregnancy negatively impacts their health and their babies, also gives socio-economics impacts and risks of premature birth, low birth weight (LBW) and bleeding that can increase maternal and infant mortality. This study aims to determine the relationship of education level with the pregnancy at the age of adolescence. This research using observational analytic design with cross-sectional to recognize the relationship between education level ties and pregnancy at the age of adolescence. The subject of this research is pregnant women in the North Coast Region of Indramayu who meet the inclusion criteria and are willing to sign the consent form after being given an explanation. The samples of 200 pregnant women were taken using consecutive sampling. The results obtained p-value = 0.045 smaller than the alpha value (<0. 05) it can be concluded that there is a relationship between the level of education of mothers with pregnancy in adolescence. Analysis we found the value of OR of 3.336 (95% CI 1.098 to 10.140) means, less educated mother 3.336 times risk higher to get married and pregnant at the age of adolescence. It is expected that health center, government worker and the Office of Religious Affairs (KUA) able to work together to provide better education for adolescents and prospective brides in order not to get pregnant at an early age.